Hospitalized Coronavirus Disease 2019 (Covid-19) with Pre-existing Diabetes Mellitus: Comparison between Survived and Deceased Patients (Bangladesh Journal of Microbiology, 2023)
Patients with pre-existing diabetes mellitus (DM) are at high risk of severe outcomes from coronavirus disease 2019 (COVID-19). However, there is limited data on these patients from South Asia, especially Bangladesh. Besides, comparative studies between survived and deceased patients with DM and COVID-19 are rare in literature. This retrospective cross-sectional study was conducted among RT-PCR confirmed COVID-19 patients with pre-existing DM in a specialized COVID-19 hospital in Bangladesh. Data from hospital records were analyzed. Among 921 RT-PCR confirmed patients with COVID-19 admitted during the study period, 231 (~25%) patients had pre-existing DM. The overall mortality and intensive care unit (ICU) mortality rate among patients with DM was 11.3% (26/231) and 46.2% (12/26), respectively. The median age of the deceased patients was slightly higher (63.5 vs. 59 years, p 0.21). The most common comorbidity in both groups was hypertension. The clinical features were not significantly different between survived and deceased. However, deceased patients had significantly lower blood oxygen level (85% vs. 93%, p